2010
DOI: 10.1111/igc.0b013e3181c54fc5
|View full text |Cite
|
Sign up to set email alerts
|

Serum Vascular Endothelial Growth Factor and Adiponectin Levels in Patients With Benign and Malignant Gynecological Diseases

Abstract: This is one of the first report on adiponectin in benign and malignant gynecological diseases. Future studies are needed to address the clinical potential role of adiponectin in cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…COX-2 inhibitors suppress the expression and secretion of MMP-2 and-9, suggesting that COX-2 also promotes tumour angiogenesis and tumour invasion. Furthermore, it was also reported that the downstream products of COX-2 stimulate VEGF to promote angiogenesis 30 . Taken together, our studies suggest that the decrease in angiogenesis by DATS may be due to the reduction in COX-2, VEGF which leads to the inhibition of MMP-2, -7 and -9 and inhibition of migration and invasion (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…COX-2 inhibitors suppress the expression and secretion of MMP-2 and-9, suggesting that COX-2 also promotes tumour angiogenesis and tumour invasion. Furthermore, it was also reported that the downstream products of COX-2 stimulate VEGF to promote angiogenesis 30 . Taken together, our studies suggest that the decrease in angiogenesis by DATS may be due to the reduction in COX-2, VEGF which leads to the inhibition of MMP-2, -7 and -9 and inhibition of migration and invasion (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…A) in HT‐29 cells. It was reported that the overexpression of COX‐II is associated with the initiation of angiogenesis and COX‐2 inhibitors can block angiogenesis . COX‐2 inhibitors suppress the expression and secretion of MMP‐2 and‐9, suggesting that COX‐2 also promotes tumour angiogenesis and tumour invasion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2004, Ashizawa et al . 2010, Lasalandra et al . 2010) that measured adiponectin found evidence for an association with endometrial cancer risk.…”
Section: Discussionmentioning
confidence: 99%
“…[ 41 ] Furthermore, evidence suggested that the inflammatory cytokine of COX-2 could promote tumor angiogenesis and tumor invasion, and the downregulation of COX-2 inhibited cancer metastasis through preventing migration and invasion. [ 42 43 ] IL-6, linking the relationship between inflammation and cancer, was an indispensable inflammatory cytokines for cancer cell proliferation and invasion. [ 44 45 ] In the present study, we demonstrated that the levels of inflammation factors of TNF-α, COX-2, and IL-6 in cell supernatant were suppressed by quercetin in a dose-dependent manner.…”
Section: Discussionmentioning
confidence: 99%